2008
DOI: 10.1103/physrevb.77.245120
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence for hidden one-dimensional Fermi surface of hexagonalK0.25WO3

Abstract: The electronic structure of hexagonal potassium tungsten bronze K 0.25 WO 3 has been investigated by highresolution angle-resolved photoemission spectroscopy ͑ARPES͒. The experimentally determined band structure resolves the long-standing puzzles concerning the anomalous transport properties in this hexagonal bronze. We find that the ARPES-derived Fermi surface is the consequence of hidden one-dimensional ͑1D͒ bands, in good agreement with the calculated Fermi surface. These results indicate that the high-temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 36 publications
(30 reference statements)
2
20
0
Order By: Relevance
“…However, recent studies have revisited the interest in these bronzes using angle-resolved photoelectron spectroscopy ͑ARPES͒ and revealed many interesting electronic structure related properties. 13 Particularly ARPES on x = 0.25 samples revealed the presence of a hidden 1D Fermi surface in conjunction with FS nesting, which is typically observed in charge-density-wave materials. 13 The observation of superlattice reflection by powder neutron-diffraction 27 and electron diffraction 10 experiments indeed support the possibility of Fermi-surface nesting accompanied by a CDW formation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent studies have revisited the interest in these bronzes using angle-resolved photoelectron spectroscopy ͑ARPES͒ and revealed many interesting electronic structure related properties. 13 Particularly ARPES on x = 0.25 samples revealed the presence of a hidden 1D Fermi surface in conjunction with FS nesting, which is typically observed in charge-density-wave materials. 13 The observation of superlattice reflection by powder neutron-diffraction 27 and electron diffraction 10 experiments indeed support the possibility of Fermi-surface nesting accompanied by a CDW formation.…”
Section: Discussionmentioning
confidence: 99%
“…13 Particularly ARPES on x = 0.25 samples revealed the presence of a hidden 1D Fermi surface in conjunction with FS nesting, which is typically observed in charge-density-wave materials. 13 The observation of superlattice reflection by powder neutron-diffraction 27 and electron diffraction 10 experiments indeed support the possibility of Fermi-surface nesting accompanied by a CDW formation. The FS nesting in only one particular direction ͓⌫͑M͔͒ for x = 0.25 revealed by ARPES suggests a weak FS instability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A channel structure is formed by cornerlinked WO 6 octahedra, with K-atom sites within the channel fully occupied when x = 0.33 and partially occupied when x < 0.33 (Magné li, 1953;Dickens & Whittingham, 1968;Hussain et al, 1978;Magneli & Blomberg, 1951). Previous studies revealed that the electric transport properties are closely related to the proportion of K in K x WO 3 (Krause et al, 1985;Sato et al, 1983;Raj et al, 2008;Sagar et al, 2010). For instance, the superconducting transition temperature (T c ) exhibited a discontinuity at x = 0.25 (Cadwell et al, 1981).…”
Section: Introductionmentioning
confidence: 96%
“…Recently, Raj et al [7] have reported angleresolved photoemission spectroscopy (ARPES) and firstprinciples density functional theory (DFT) results concerning the FS of the hexagonal potassium tungsten bronze, K 0.25 WO 3 [8] (see Fig. 1(a)).…”
mentioning
confidence: 99%